1993
DOI: 10.1007/bf00033772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inoculum density and temperature on three components of leaf rust resistance controlled by Lr34 in wheat

Abstract: Different inoculum densities had negligible effects on latent period, uredinium density and uredinium size measured on flag leaves of adult RL6058 (Thatcher* 6/PI58548 [Lr34]) plants kept at low (17.5 ° C) post-infection temperatures in a glasshouse. In a qualitative assessment of rust severity at higher (24.6°C) temperatures, all three components of resistance indicated a susceptible flag leaf response on RL6058. In the latter environment, precise estimations of receptivity to different inoculum densities sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…latent period and smaller uredinia, but not reflected by infection types, in the line T34-13-5/1 inoculated with UVPrt13. The reliability of the individual components as measures of resistance was discussed in several studies (Broers & Wallenburg, 1989;Drijepondt & Pretorius, 1989;Jacobs & Kiriswa 1993;Pretorius et al, 1994). In the present study, a longer latent period appeared related to smaller and fewer uredinia of UVPrt13 on T34-13-5/1.…”
Section: Infection Types and Disease Severitysupporting
confidence: 62%
See 2 more Smart Citations
“…latent period and smaller uredinia, but not reflected by infection types, in the line T34-13-5/1 inoculated with UVPrt13. The reliability of the individual components as measures of resistance was discussed in several studies (Broers & Wallenburg, 1989;Drijepondt & Pretorius, 1989;Jacobs & Kiriswa 1993;Pretorius et al, 1994). In the present study, a longer latent period appeared related to smaller and fewer uredinia of UVPrt13 on T34-13-5/1.…”
Section: Infection Types and Disease Severitysupporting
confidence: 62%
“…No pathotypes of P. recondita with virulence for adult plants of lines possessing Lr37 have been reported from southern Africa (Pretorius et al, 1990;Kloppers & Pretorius, 1994). However, pathotype UVPrt2 possessed slightly greater virulence (;1 cn ) than UVPrt13 (; cn ) on T37.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…studied slow rusting components in bread wheat and found that temperature and growth stage had little effect on uredinium size. Pretorius et al (1994) did not find an effect of inoculum concentration on uredinium size. In addition, Das et al (1993) showed that the narrow sense heritability of uredinium size was higher than that for latent period and receptivity, meaning that breeding for slow rusting resistance in bread wheat would be more efficient if selection is based on this component rather than on the other two.…”
Section: Discussionmentioning
confidence: 69%
“…The Lr34/Yr18 gene for resistance to leaf and stripe rust has been shown to be very important in durable rust resistance in wheat (Lagudah et al, 2009). Some of the early work on the Lr34 phenotype, which showed that the gene is detectable in seedlings at low temperatures and that several resistance components interact in adult plants, was done in South Africa (Drijepondt & Pretorius, 1989;1991;Pretorius et al, 1994). In addition, Kloppers and Pretorius (1997) quantified the effect of gene combinations involving Lr13, Lr34 and Lr37 in reducing leaf rust infection in adult plants.…”
Section: Wheat Rustsmentioning
confidence: 99%